Digital libraries principles and practices in a global environment - Tedd, Lucy A. (Gale virtual reference library, 2005)
"A concise and easily digestible introduction to a range of international, digital library-related developments for graduate and undergraduate students in Library Science, Information Science or Computer Science (and related) programs around the world, as well as information professionals working in libraries and information units who wish to update their knowledge in this rapidly developing field."--GVRL description.